Comparison and Analysis of Routing Protocols Using Riverbed Modeler - Mahdi Ali Warsame; Abdullah Sevin (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In recent years several routing protocols have beenproposed to be used on different types of networks. Some comparative studieswere carried out to analyze and compare the performance of several routingprotocols over Local Area Network (LAN). In this work, RIP, EIGRP, OSPF routingprotocols were analyzed, compared and simulated over Riverbed Modeler. Theperformance of different protocols are compared using Riverbed Modeler tool inwhich metrics like delay, throughput, and convergence time are measured. Thebehavior of the protocols over different network topologies and different datarates were analyzed.